Metabolism, and rumen microbiome of Nellore beef cattle submitted to intensified grazing systems during different season - Andrade, Willian Rufino (2023)
In order to assess alternatives that can mitigate the environmental impact of beef cattle production, this study aimed to evaluate whether intensifying the grazing system in conjunction with ammonium nitrate supplementation could alter ruminal metabolism and reduce methane emissions from animals kept in grazing systems. The specific objectives were to measure the effects of grazing methods and supplements on dry matter intake, digestibility, degradability parameters, ruminal pH, concentration and production of fermentation metabolites, microbial protein synthesis, and ruminal microbiota. Eight cannulated Nellore cows were randomly allocated to eight paddocks in a randomized block design with a factorial arrangement formed by the nitrogen source (ammonium nitrate or urea), grazing method (rotational or deferred), and seasons. The treatments consisted of the combination of two grazing methods, deferred or rotational, with supplementation of either ammonium nitrate or urea. Variables such as dry matter intake, digestibility, dry matter, protein, and neutral detergent fiber degradability parameters, ruminal emptying, production and concentrations of short-chain fatty acids, methane, ammonia nitrogen, urinary parameters, and protozoa count were evaluated using the PROC MIXED procedure of SAS 9.4. However, the degradability parameters were first obtained using the linear procedure (PROC NLIN). Data related to ruminal microbiota were analyzed using the Mothur software, R, and SAS 9.4. The results showed that animals kept in rotational grazing had higher non-protein nitrogen intake, but no effect of nitrogen source was observed for supplement intake. However, when urea and nitrate were used as the main nitrogen sources, both equally contributed to microbial protein synthesis and its efficiency. Nitrate supplementation reduced ruminal energy release in the form of acetic acid by 23.13% during the Summer. Butyric acid concentrations were higher in animals under rotational grazing systems in the Spring and Autumn. The study also observed a 13.1% reduction in methane production and a subsequent 15.7% decrease in ruminal energy release in animals supplemented with nitrate compared to urea. Rotational grazing systems contributed to a 21.3% reduction in methane production during the Summer season. Microorganisms from the Methanobacteriaceae family showed higher relative abundance in the rumen of animals kept in deferred grazing, and nitrate supplementation significantly decreased their abundance. Nitrate supplementation had an impact on specific groups of bacteria and archaea, with bacteria from the Veillonellaceae family showing an increase in relative abundance, while inhibiting archaea belonging to the Methanobacteriaceae family. Adoption of rotational grazing and nitrate supplementation proves to be a great alternative for the intensification of pasture-based beef cattle production, allowing slight improvements in diet digestibility, increased non-protein nitrogen intake, providing greater ruminal energy supply, and mitigating enteric methane emissions.